Implementation of Tamarind and Red Ginger Boiled Drink to Reduce Dysmenorrhea in Adolescent Girls - Marlefi, Nisa Nur; Oktavianti, Dewi Siti (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Dysmenorrhea is pain that a person feels during menstruation. Dysmenorrhea in adolescent females can adversely affect the learning process, as menstrual discomfort often impairs concentration and cognitive engagement. In more severe cases, the intensity of pain may necessitate rest, resulting in school absenteeism. Consequently, effective management of menstrual pain is essential to minimize its impact on daily functioning and to support the academic and psychosocial well-being of affected adolescents. This study aims to find out the difference between the administration of tamarind turmeric and red ginger decoctions on menstrual pain (dysmenorrhea) in adolescent girls. The design of the study used a quasi-experiment with two group pretest-posttest design. The population of this study was adolescents girl of classes VII, VIII, and IX, of 115 people. The total sample of this study was 40 people, consisting of two groups of 20 people in the tamarind turmeric group and 20 in the red-ginger group. The sampling technique used was stratified random sampling. This research instrument used the Numeric Rating Scale questionnaire (NRS). Statistical test using independent t test, with p value: 0,397, indicating that there was no significant difference in dysmenorrhea after the intervention between the turmeric-tamarind group and the red ginger group. Both turmeric-tamarind and red ginger decoctions can be one of the non-pharmacological therapies to help reduce menstrual pain (dysmenorrhea).